Peramivir Susceptibilities of Recombinant Influenza A and B Variants Selected with Various Neuraminidase Inhibitors. Issue 8 (November 2017) - Fage, Clément; Tu, Véronique; Carbonneau, Julie; Abed, Yacine; Boivin, Guy
Background: Peramivir is a parenteral neuraminidase inhibitor (NAI) approved for treating influenza infections in a few countries. We determined peramivir susceptibilities of several uncharacterized influenza A and B neuraminidase (NA) and haemagglutinin (HA) mutants selected with different NAIs. Methods: Recombinant wild-type (WT) and mutant NA proteins were expressed in 293T cells and susceptibility to peramivir, oseltamivir and zanamivir was determined by NA inhibition assay using the MUNANA substrate. Recombinant/reassortant influenza A(H1N1), A(H3N2) and B HA mutants were rescued by reverse genetics and assessed by plaque size or viral yield assays for drug susceptibility. Results: Recombinant R152K, I222K/T, G248R+I266V, Q312R+I427T and R371K (A[H1N1]pdm09); E41G, 1222L/V, Q226H and S247P (A[H3N2]) and D198Y, A246D/S/T and G402S (B) mutant NA proteins (N2 numbering) were analysed. Peramivir exhibited the lowest IC50 values against both influenza A and B WT NAs. Peramivir and oseltamivir generally shared similar phenotypes. Of note, peramivir retained activity against I222K/T (A[H1N1]pdm09), I222L/V (A[H3N2]) and A246T (B) mutants, which had reduced inhibition (RI) or highly RI (HRI) against oseltamivir. Cross-RI/HRI against the three NAIs was observed for R152K, R371K and Q312R+I427T (A[H1N1]pdm09); S247P (A[H3N2]) and D198Y (B) mutants. All tested recombinant/reassortant R208K (A/ Puerto Rico/8/34 [H1N1]); A28T, R124M and K189E (A/ Victoria/3/75 [H3N2]) and T139N (B/Phuket/3073/13) HA mutants were susceptible to peramivir in cell culture experiments. Conclusions: Peramivir is highly active against seasonal influenza subtypes. Although peramivir and oseltamivir generally share similar phenotypes, peramivir still possesses activity against some variants with RI/HRI against oseltamivir. Finally, NAI-induced HA substitutions alone did not significantly impact NAI susceptibility.